Visual communication design : an introduction to design concepts in everyday experience - Davis, Meredith (Meredith J.); Hunt, Jamer (London : Bloomsbury Visual Arts, 2017)
"This is a foundation level textbook for courses in basic design and introductory courses in visual communication design. The chapters in this book follow the user experience cycle: attention, orientation, interpretation and extension and retention of meaning. Each chapter includes an introduction to the interpretive task, definitions of the elements and principles related to the task, illustrations and diagrams plus examples of professional design work that makes use of the element or principle. For example, Chapter 2 on getting attention discusses the various ways that design can capture the viewer's eye such as by using proportion, contract, color, pattern, etc"--
Keywords: Design -- Textbooks; Visual communication -- Textbooks; DESIGN / General; DESIGN / Graphic Arts / General